YITNA YUWANA LENA KENA IN GOGROKE RERONCEN KEMBANG GARING’S NOVEL BY TULUS SETIYADI - Mayanfauli, Arauni; Darmoko, Darmoko (UI Scholars Hub, 2019)
Language expressions in Javanese culture that contain a warning to someone at the moment and will do an activity or work are often formulated with the word structure: yitna yuwana lena kena. The idea in the phrase is usually related to ethical values (moral philosophy) how one must be careful in speaking, behaving, and acting so that someone gets the safety of life in the world. Conversely, if someone is not careful in speaking, acting, and acting undoubtedly will get problems in his life. Ethical values in this novel relate to moral teachings to a woman so that she always has virtues, such as carrying herself well, must be able to hold back the passions, predict and consider things that are and will be faced, which are good and not good, and not permitted excessive behavior. Objective approach, qualitative descriptive research method and Javanese ethical theoretical conceptual framework from Franz Magnis Suseno is used to examine the text in the yitna yuwana lena kena language expression in the Gogroke Reroncen Kembang Garing’s novel. An ethical conceptual framework is used to assess the karma experienced by the main character. The assumption in this study says that the words, attitudes, and actions of someone who is careless and despicable will have an impact on suffering and misery.